MANIFESTASI PRESENCE OF STATE: LEGALITAS POLSEK SEBAGAI PIONIR STABILITAS KEAMANAN DALAM NEGERI - Boini, Usman; Ardiyansyah, Amzar; Gibran, Khalil; Nazaruddin, Nazaruddin (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2026)
This study analyzes the strategic legal position of Security Intelligence (Intelkam) at the Sector Police (Polsek) level as the spearhead of the state in carrying out early detection and early warning functions. The research method used is normative juridical with a statutory and conceptual approach through qualitative analysis of literature and related reports. Normatively, this role has a strong constitutional basis in Article 30 paragraph (4) of the 1945 Constitution of the Republic of Indonesia and Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia, which positions the Polri as a state instrument in maintaining security through preventive measures. The implementation of preventive policies through mapping potential vulnerabilities, especially regarding mass mobilization and political dynamics, has proven crucial in preventing horizontal conflict at the grassroots level, as in the case study that occurred at the Mutiara Timur Police. However, in its implementation, obstacles are still found related to the limitations of authority and technological challenges. This study suggests strengthening operational regulations through synchronizing more specific derivative rules to provide legal certainty for members in the field and avoid overlapping authority and the risk of human rights violations. Furthermore, human resource capacity building and cyber intelligence technology support are needed at the police sector level to anticipate the threat of black campaigns on social media. Optimizing cross-sectoral synergy through a humanistic approach is expected to strengthen national security stability from the smallest regional level.